Diplomatarium Danicum 3. r., 9. bd.. 1371-1375. (C.A. Reitzels Forlag, 1982). 530 s. Danmarks Riges breve 3.r., 9. bd., 1371-1375. (C.A. Reitzels Forlag, 1982). 402 s. - Søgaard, Helge (Historie/Jyske Samlinger, 1985)
-